Reversible p53 inhibition prevents cisplatin ototoxicity without blocking chemotherapeutic efficacy - Nesrine Benkafadar; Julien Menardo; Jérôme Bourien; Régis Nouvian; Florence François; Didier Decaudin; Domenico Maiorano; Jean‐Luc Puel; Jing Wang (EMBO Molecular Medicine)
Abstract Cisplatin is a widely used chemotherapy drug, despite its significant ototoxic side effects. To date, the mechanism of cisplatin‐induced ototoxicity remains unclear, and hearing preservation during cisplatin‐based chemotherapy in patients is lacking. We found activation of the ATM‐Chk2‐p53 pathway to be a major determinant of cisplatin ototoxicity. However, prevention of cisplatin‐induced ototoxicity is hampered by opposite effects of ATM activation upon sensory hair cells: promoting both outer hair cell death and inner hair cell survival. Encouragingly, however, genetic or pharmacological ablation of p53 substantially attenuated cochlear cell apoptosis, thus preserving hearing. Importantly, systemic administration of a p53 inhibitor in mice bearing patient‐derived triple‐negative breast cancer protected auditory function, without compromising the anti‐tumor efficacy of cisplatin. Altogether, these findings highlight a novel and effective strategy for hearing protection in cisplatin‐based chemotherapy.